USE OF ENZYMES IN BREEDING AND FATTENING OF BROILERS IN RAINY SEASON IN QUEVEDO,SALCEDO AND SANTO DOMINGO DE LOS COLORADOS - Luna Murillo, Ricardo (2010)
With the purpose of evaluating the use of commercial enzymes Ronozyme, SSF, VegPro and Hyboteck (Yucca schidigera) in the growing and weigth gain of broilers chickens in rainy time a trial was settled down in three provinces: Los Ríos (Quevedo), Santo Domingo of the Tsáchilas (Santo Domingo de los Colorados) and in Cotopaxi (Salcedo), using a total of 1440 of Hubbard line (480 for locality). A totally randomize design was used with four treatments (enzymes) and six repetitions with 20 chickens as experimental unit. The valued variables were: food consumption (g), weight gain (g), feed conversion, yield at the canal (%) and cost / benefit relationship. It was observed that the major consumptions of food in the three towns presented with Hyboteck, (5,181.21; 6,713.42 and 5,680.37 g) the better weight gain was observed with the enzyme Vegro in Quevedo (2,543,34 g), SSF Santo Domingo de los Colorados (34987,83 g) and Hyboteck in Salcedo (2,286.08 g) the most efficient conversion was reported with Ronozyme in Quevedo (1,76), SSF in Santo Domingo de los Colorados (1.88), and VegPro in Salcedo (2.55). The major relationship cost /benefit was presented with SSF in the towns of Santo Domingo de los Colorados (0,10) and Salcedo (0.21) while in Quevedo the better was Ronozyme (0.26). The major nutritional value in the channels of the chickens was reported in the towns of Quevedo and Salcedo with Ronozyme (26, 05 and 22.80% protein respectively), while for Santo Domingo de los Colorados town was with SSF (25.35% of protein).